2003
DOI: 10.1038/sj.onc.1206199
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the tight junction protein claudin-7 correlates with histological grade in both ductal carcinoma in situ and invasive ductal carcinoma of the breast

Abstract: Claudins are transmembrane proteins that seal tight junctions, and are critical for maintaining cell-to-cell adhesion in epithelial cell sheets. However, their role in cancer progression remains largely unexplored. Here, we report that Claudin-7 (CLDN-7) expression is lower in invasive ductal carcinomas (IDC) of the breast than in normal breast epithelium, as determined by both RT-PCR (9/10) and Western analysis (6/8). Immunohistochemical (IHC) analysis of ductal carcinoma in situ (DCIS) and IDC showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
400
5
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(437 citation statements)
references
References 21 publications
29
400
5
3
Order By: Relevance
“…We observe a selection for the loss of occludin and claudins-3, -4 and -7 in the liveraggressive breast cancer cell populations. These observations are consistent with a loss of claudin-1 and -7 expression in primary breast cancers of increasing grade (Kramer et al, 2000;Kominsky et al, 2003;Sauer et al, 2005). Our results are also in agreement with a recent publication demonstrating the loss of cell adhesion molecules, including claudin-4 and claudin-7, in 4T1 sub-populations that are metastatic to the liver (Erin et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observe a selection for the loss of occludin and claudins-3, -4 and -7 in the liveraggressive breast cancer cell populations. These observations are consistent with a loss of claudin-1 and -7 expression in primary breast cancers of increasing grade (Kramer et al, 2000;Kominsky et al, 2003;Sauer et al, 2005). Our results are also in agreement with a recent publication demonstrating the loss of cell adhesion molecules, including claudin-4 and claudin-7, in 4T1 sub-populations that are metastatic to the liver (Erin et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies demonstrate the loss of specific claudins during breast cancer progression, whereas others suggest that overexpression of particular claudins are associated with poor outcome in breast cancer patients (Martin and Jiang, 2009). For example, some breast cancers exhibit a loss of claudin expression, including claudin-1, -2 and -7 (Kominsky et al, 2003;Sauer et al, 2005;Tokes et al, 2005;Kim et al, 2008), whereas claudin-3 and -4 can be overexpressed in human breast cancers, particularly in the triple-negative subtype (Kominsky et al, 2004;Blanchard et al, 2009;Kulka et al, 2009;Lanigan et al, 2009). Although these studies, which are focused on claudin expression in the primary tumor, suggest that specific claudin proteins may fulfill tumor-suppressor or tumor-promoting roles in breast cancer, little is known regarding claudin expression in breast cancer metastases.…”
Section: Introductionmentioning
confidence: 99%
“…CLDN-3 and CLDN-4 are upregulated in ovarian and uterine cancers, 10,17,35,36 and CLDN-4 expression has been exploited for therapeutic purposes. 24 CLDN-7 expression is decreased in breast carcinomas, 13,37 but Adenocarcinoma vs bronchial cell (n ¼ 6) upregulated in gastric carcinomas. 9 With regards to other tight junction membrane proteins, we observed a statistically significant decrease in JAM-1 transcript levels in squamous cell carcinoma, when compared with normal bronchial cells, and in OCLN mRNA in squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an altered expression of CLDNs in human tumors, including tumors of the gastrointestinal tract, 8,9 ovary, 10 pancreas, 11 breast, 12,13 epidermis, 14 liver, 15,16 uterus 17 and prostate. 18 Little information is available on the expression of cytoplasmic tight junction proteins in human cancers, [19][20][21][22] and only one study has been published about the immunohistochemical localization of a tight junction protein (occludin (OCLN)) in lung tumors.…”
mentioning
confidence: 99%
“…So far, claudin-1,3,4,5,7,10,16 have been shown altered in various cancers [5]. The functions of these proteins in tumorigenesis are still being elucidated, but they may have important roles in cell survival, motility, and invasion of cancer cells [18][19][20]. The mechanisms leading to the overexpression of claudins in cancer as well as the mechanisms of post-translational regulation/ modification of these proteins in cancer are not well understood.…”
Section: Introductionmentioning
confidence: 99%